Mast Cell Neural Interactions in Health and Disease - Mittal, Aditya; Sagi, Varun; Gupta, Mihir; Gupta, Kalpna (Frontiers in Cellular Neuroscience, 2019)
Mast cells are located in the periphery as well as the central nervous system (CNS). Known for sterile inflammation, mast cells play a critical role in neuroinflammation, which is facilitated by their close proximity to nerve fibers in the periphery and meninges of the spinal cord and the brain. Multifaceted activation of mast cells releasing neuropeptides, cytokines and other mediators has direct effects on the neural system as well as neurovascular interactions. Emerging studies have identified the release of extracellular traps, a phenomenon traditionally meant to ensnare invading pathogens, as a cause of mast cell-induced neural injury. In this review, we will discuss mechanisms of mast cell interaction with the nervous system through degranulation, de novo synthesis, extracellular vesicles, tunneling nanotubes, and extracellular traps with implications across a variety of pathological conditions.